THE IMPLEMENTATION OF ACCRUAL ACCOUNTING IN HIGHER EDUCATION INSTITUTION: A MULTIPLE CASE STUDY OF STATE ISLAMIC UNIVERSITIES - Sulistiani, Dwi (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
This study aims to determine the implementation of accrual accounting in State Islamic University, focus on the process of preparation of the financial statements: definition, recognition, measurement, recording, presentation, and disclosure. This qualitative research with multiple case study approaches takes the two sites of State Islamic University (UIN) with public service status (BLU). The research data are obtained through an interview, observation, and documentation that analyzed by content analysis. The results showed that UIN is still not yet applying accrual accounting thoroughly. The definition and measurement are following the Government Accounting Standards (SAP) but not under Financial Accounting Standards (SAK). The financial statements presented by SAP and SAK. The recognition, recording, and disclosure are still not accrual-based for most transactions. There are obstacles in its implementation: competence inadequacy of human resources, require a support system of integrated accounting, coordination inadequacy, and leadership commitment. The use of technology must be balanced with competent human resources so that accrual accounting can be implemented properly. The results of this research have implications for the need to increase human resource capacity, especially understanding of accrual accounting at state Islamic universities.